THE NATURE OF INHERITANCE OF THE COLORED COTTON FIBER TRAIT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article provides information on the biology of diploid and tetraploid cotton species, character and patterns of inheritance of fiber color. The fabric obtained from naturally colored cotton fibers has the properties of greater hygiene and hypoallergenic. Clothing made from such a fabric does not cause irritation on the skin, as the fabric perfectly passes air.